Measurements of the natural plasma flow during the precursor of TCABR density limit disruptions - F. Salzedas (2015)
Magnetic islands are known to degrade confinement of energy and particles in tokamak plasmas. They are also present in the precursor of density limit disruptions being observed until the onset of the energy quench of the disruption. The subject of the effect of plasma flow on tearing mode stability has been studied both theoretically [1] and experimentally [2]. However the experimental work has focused on plasmas with Neutral Beam Injection (NBI), which adds high momentum to both the plasma and the island, deviating them from their natural velocities. It is important to know the plasma/island rotation behavior without NBI, not just to know their natural values but because future large tokamaks, like ITER, are expected to have low plasma rotation due to both large plasma inertia and low applied torque. In this work we will show experimental values of the ion velocity and the magnetic island velocity measured in TCABR ohmic plasmas, without NBI, and during the precursor of a density limit disruption. In this way it was possible to compare the natural plasma velocity with the island velocity. The ion velocity was inferred from Doppler spectroscopy of the impurity lines of CVI. Details of this diagnostic system and an error analysis of the measured signal can be found in [3]. With the present set up, the toroidal velocity can be measured with time resolution equivalent to 600 Hz and precision somewhat better than 5 km/s.